OPTIMALISASI LAHAN SUBOPTIMAL DI KABUPATEN PANGKEP MELALUI ZONASI TANAMAN KACANG TANAH (Arachis hypogaea L.) BERBASIS CARRYING CAPACITY - Jumarsa, Jumarsa; Nurmiaty, Nurmiaty; Agustia, Monika (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2025)
Suboptimal land in Pangkep Regency has the potential for developing peanut plants. However, the utilization of this suboptimal land is still not optimal due to limited information on land suitability and its carrying capacity. This study aims to optimize suboptimal land in Pangkep Regency through zoning of peanut plants based on carrying capacity using spatial analysis methods with Arc-GIS processing devices, digital land system data from Pangkep Regency. The suitability parameters for peanut plants that are determined and analyzed include 8 regional characteristics, namely Temperature, Drainage, Texture, Base Saturation, PH H2O, C-organic, Salinity, and Slope, to determine the land suitability class consisting of very suitable classes (S1), Suitable/fairly suitable (S2), marginally suitable (S3), or not suitable (N). Spatial analysis utilizes the Map calculator facility in Arc-GIS software (Arc View Gis) to match the suitability of each characteristic in Pangkep Regency with the requirements for growing peanut plants based on land suitability criteria. The results of the study indicate that (1) The Land Suitability Level Criteria for peanut plants in Pangkep Regency is the class according to the land suitability class level for peanut plants in Pangkep Regency is the Very Suitable Class (S1) Quite Suitable (S2), Marginally Suitable (S3) and Not Suitable Class (N). (2) The spatial distribution data obtained for the suitability of peanut plants in Pangkep Regency is the Very Suitable Class (S1) of 116,74 ha, Quite Suitable (S2) of 522,47 ha, Marginally Suitable (S3) of 31.718,93 ha, spread across 9 sub-districts in Pangkep Regency. While other suitability classes are Not Suitable (N) of 47.673,93 ha,